2019
DOI: 10.1136/medhum-2018-011639
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and the emotions in 18th-century literature

Abstract: This essay argues that the emotional rhetoric of today’s breast cancer discourse—with its emphasis on stoicism and ‘positive thinking’ in the cancer patient, and its use of sympathetic feeling to encourage charitable giving—has its roots in the long 18th century. While cancer had long been connected with the emotions, 18th-century literature saw it associated with both ‘positive’ and ‘negative’ feelings, and metaphors describing jealousy, love and other sentiments as ‘like a cancer’ were used to highlight the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Sontag 33 highlighted that cancer has long been associated with repression and mismanagement of emotions. Gallegher 34 maintain that these ideas began to popularize in the XVIII century with their incorporation into the literary portraits of the time. In these stories, patients with cancer were characterized as people who were prey to emotions such as pain, anger, and envy; emotions that they were unable to handle and caused the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sontag 33 highlighted that cancer has long been associated with repression and mismanagement of emotions. Gallegher 34 maintain that these ideas began to popularize in the XVIII century with their incorporation into the literary portraits of the time. In these stories, patients with cancer were characterized as people who were prey to emotions such as pain, anger, and envy; emotions that they were unable to handle and caused the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In these stories, patients with cancer were characterized as people who were prey to emotions such as pain, anger, and envy; emotions that they were unable to handle and caused the disease. As in the novels of the XVIII century, today’s self-help books establish the link between these emotions and the etiology of the disease; therefore, there is still pressure to reduce or destroy the expressions of sadness, fear, anger, and despair 34 to maintain “positive thinking” and hold patients with cancer responsible for their illness if they fail to do so. 10 Notably, these narratives contribute to legitimizing the idea of individual responsibility in the etiology of cancer, the omission of structural problem management, and the lack of attention paid by the state to its responsibility for the common good, ideas that are in line with the interests of neoliberal government rationalities 35 but are contrary to the medical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by He et al [ 11 ] which included 200 BC patients, it was found that patients' negative emotions, such as depression and anxiety, were significantly reduced after emotional management, and the recovery of BC patients was good. Many studies have also found that negative emotions greatly affect the incidence of BC[ 12 - 15 ]. In a study by Xu et al [ 12 ] a total of 9343 studies were screened, aiming to explore the connection between negative emotions and the incidence of BC, as well as possible risk factors.…”
Section: Negative Emotions and Breast Cancermentioning
confidence: 99%
“…35. N Gallagher (2020), ”Cancer and the Emotions in 18th-Century Literature,” Medical Humanities 46, no. 3. doi:10.1136/medhum-2018-011639, 2.…”
mentioning
confidence: 99%